2012
DOI: 10.1159/000341540
|View full text |Cite
|
Sign up to set email alerts
|

Selbstregulation bei Essstörungen und Adipositas – Implikationen für die Behandlung

Abstract: Die Forschung hat gezeigt, dass die Behandlung einzelner Essstörungen wie z.B. der Anorexia nervosa und ungünstigen Essverhaltens bei Adipositas nur begrenzt effektiv ist bzw. dass auch nach Behandlung der Essstörungssymptomatik eine erhöhte Psychopathologie bestehen kann. Daraus ergibt sich die Notwendigkeit, weitere ätiologische und aufrechterhaltende Faktoren zu identifizieren, deren Veränderung die Wirksamkeit der Behandlung optimieren könnte. Ziel des vorliegenden narrativen Reviews ist es, anhand aktuell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Subjectively perceived stressors in the parental relationship are hypothesized to increase the risk for psychosocial maladaptation and the occurrence of EDs [ 9 ]. Furthermore, the development of abilities to regulate emotions and impulses is influenced by the parental relationship [ 10 ] and the capacity to self-regulate was shown to be negatively affected by stronger parental control [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjectively perceived stressors in the parental relationship are hypothesized to increase the risk for psychosocial maladaptation and the occurrence of EDs [ 9 ]. Furthermore, the development of abilities to regulate emotions and impulses is influenced by the parental relationship [ 10 ] and the capacity to self-regulate was shown to be negatively affected by stronger parental control [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that during feeding, when the relationship between children and parents is not able to coordinate and share sensitive interactions, the infant will not be able to learn the self-regulation of affects and may show maladaptive emotional and behavioural symptoms over time [ 13 ]. These parenting practices and their influence on children's emotional as well as food self-regulation abilities [ 14 ] are believed to play an important role in the development and maintenance of EDs [ 10 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eating disorders (EDs) are associated with a reduced ability to regulate emotion and impulses during the lifespan [1]. Food assumption and appetite, defined as the motivational drive to obtain food, are subordinated by the basal regulation of hunger and fullness.…”
Section: Cognitive and Emotional Regulation In Adolescents And Young mentioning
confidence: 99%
“…The term of self-regulation is described in connection to well-being (Baumann, Kaschel, & Kuhl, 2005;Hofer, Busch & Kartner, 2011) and to health management (Cameron & Leventhal, 2003;Mann, de Ridder & Fujita, 2013). The aspects of selfregulation, widely researched in the Western psychology are related to health management and well-being: eating disorders (Fischera & Munsch, 2012), alcohol consumption (Hustad, Carey, Carey & Maisto, 2009); sexual behavior (Ross & Fontao, 2006); aggressive behavior (Ross, Fontao & Schneider, 2007;Tittle, Ward & Grasmick, 2003), etc.…”
Section: Representation Of Self-regulation In Western and Russian Psymentioning
confidence: 99%